Human Coronavirus-229E, -OC43, -NL63, and -HKU1 (Coronaviridae) - Liu, Ding X. (Encyclopedia of Virology, 2021)
Seven human coronaviruses (HCoVs) have been so far identified, namely HCoV-229E, HCoV-OC43, HCoV-NL63, HCoV-HKU1, severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV) and the novel coronavirus (2019-nCoV, a.k.a. SARS-CoV-2). Unlike the highly pathogenic SARS-CoV, MERS-CoV, and 2019-nCoV, the four so-called common HCoVs generally cause mild upper-respiratory tract illness and contribute to 15%–30% of cases of common colds in human adults, although severe and life-threatening lower respiratory tract infections can sometimes occur in infants, elderly people, or immunocompromised patients. In this article, we review the molecular virology of these common HCoVs, and summarize current knowledge on HCoV-host interaction, pathogenesis, and other clinically relevant perspectives.